TINGKAT PEREKONOMIAN MASYRAKAT PETANI HORTIKULTURA DI KECAMATAN BANUHAMPU - Luklu Ul Hayati; Ratna Wilis (JURUSAN GEOGRAFI FIS UNP, 2021)
Mapping of horticultural crops is needed to determine the amount of productivity that is affected by the dry and rainy seasons. The welfare of farmers can also be measured through this mapping. For this reason, in measuring the economic level of horticultural farmers by collecting quantitative data with several correspondents of horticultural farmers in the area of Banuhampu District. So, the yield of horticultural plant productivity from summer and winter that has the highest productivity value is onion plants, while the lowest productivity is during the rainy season and in summer. For land cultivation, horticultural farmers use two methods, namely primary and secondary methods, while the land used is privately owned with seeds and toxins financed independently. However, for fertilizer, part of it is subsidized by the government in the program of adulterating farmers. The income of horticultural plant farmers who are classified as very high are shallot farmers and those with the lowest group are dominated by leek farmers. Thus, the economic level of horticultural farmers can be measured and can be a reference for farmers to choose plants to plant according to the season to be. faced so as not to experience losses.